The Role of Emotional Regulation in Enhancing Students’ Academic Motivation - Ummi Masrufah Maulidiyah; Farrel Allysia Putri Rediyanti; Mahadewi Philothra Sacharissa Sapphira; Nisa Selfina; Shenny Syahrana Maulidia Fatihah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This review examines how emotional regulation contributes to improving academic motivation in late adolescents. Teenagers frequently encounter emotional difficulties that can influence their engagement in learning and overall academic performance. By synthesizing findings from five recent international studies published between 2023 - 2024, the review highlights effective strategies, interventions, and developmental frameworks for managing emotions. Results suggest that adaptive techniques, including cognitive reappraisal, mindfulness, and self-control, positively impact intrinsic motivation, resilience, and academic outcomes while mitigating stress and burnout. These findings underscore the importance of emotional regulation in supporting adolescents’ psychological health and educational success. The study also stresses the need to integrate emotional regulation practices into school programs to enhance both motivation and long-term academic achievement.